Bibliometric Analysis: Trends In Green Marketing Research Development And Consumer Behavior Towards Sustainable Products - Eko Triawan; Nopa Dwi Saputra; Apep Indra Saputra; Rohmadi (Innovation Business Management and Accounting Journal, 2025)
This study aims to analyze research development trends on green marketing and consumer behavior towards sustainable products in the 2020-2024 period. Using bibliometric methods, this study evaluates the number of publications, citation trends, author collaboration patterns, and thematic relevance through keyword co-occurrence analysis of indexed scientific literature. The results show an increase in the number of publications each year, although the citation impact tends to be greater in early publications during the study period. Citation analysis identifies influential articles that highlight key factors in consumers' green purchasing behavior. Mapping author collaborations reveals a solid network among researchers, while keyword co-occurrence analysis identifies three main clusters focusing on the basic concepts of green marketing and sustainable consumption, green product marketing strategies, and methodological studies. The conclusions of this study underscore the importance of a deep understanding of consumer behavior in designing effective green marketing strategies and the need for further research to broaden insights in this field.